Development of a low-cost parallel computing system for digital mammograms visualization / Hanifah Sulaiman - Sulaiman, Hanifah (2010)
Parallel Computing System (PCS) is currently being used widely in many applications of complex problems in image processing. It is now a trend towards the utilization of PCS to solve intermediate and large scale mathematical problems because this system can generate the output in shorter periods as compared with sequential computing systems. Two ARS clusters which are both low-cost parallel computing systems have been developed at Pusat Pengajian Matematik using the Beowulf model. The clusters are composed of used processors and implement the open source software as the operating system which incurs no cost on the system. Both clusters are internally connected using LINUX and the standard Ethernet network.